Visualisasi Spatio Temporal Kasus Covid-19 di Kota Palembang - Heri Setianto; Eni Heldayani; Yanuar Adji Nugroho (Universitas Pendidikan Ganesha, 2021)
This research is a research with a case study approach that aims to provide a new perspective on the spread of COVID-19 cases in the city of Palembang, namely by visualizing information about the spread of COVID-19 in Palembang City in a spatio-temporal manner. Spatio means presenting the distribution of the disease in dimensions spatially by making the District administration as a mapping unit and temporal shows the speed of spreading cases from day to day. So that by combining the two, it can be seen the direction of disease spread with an increase in the number of positive sufferers, ODP and PDP and the speed of spread from day to day. Data on positive sufferers, ODP, and PDP are accessed through the official website of the Palembang City Information and Communication Service via the hallopalemabang.go.id website. Data management and analysis begins after the required data has been collected. The data is compiled into a database. The database used here is PostgreSQL. RDBMS which has the advantage in handling spatial-based databases. The historical data obtained then needs to be formatted and organized so that it fits the GIS data format. Data that is in accordance with the GIS format can be called and displayed into Mapbox. Mapbox is one of the Maps API Services which has almost the same features as the Google Maps API which is used for styling and more attractive map backgrounds. COVID-19 cases that occur in 18 districts in Palembang City have different phenomena every day. The district with the highest tight box record was Kec. Ilir Barat Satu, in second place is Kec. Kalidoni and the third are Kec. Ilir Timur One. Meanwhile, the kecamatan with the lowest record of close contact was Kec. Gandus. From Figure 2 it can be seen that there is an interesting pattern in which in July, the total close contact with confirmed cases is almost the same (95%). Meanwhile, in the months after the number of confirmed cases the number was relatively constant over time, although the number of close contacts continued to increase. As of 26 November 2020, approximately 53% of the number of close contacts were registered as confirmed cases